(3cTGas - (3GdnqRnerNnTpQj GdNhGQRej, CHh GdbGSe, LGQ Gddg, eMehO Hf YeQ Hf eMeO Hf CMeO, (B538 (3g`s
(3ChdgG (B:s
... (3CSeGA eYQHI hEfeG ScfJ Schf RjO hYeQh hZjQgeG ef GdCSeGA MjK dG jeSgG GYQGH dabO ebJVjg hehLHg hGdOdjd Ydi Gf SchfgG hba hdjS HHfGA GfgG dh HfjJ dMPi HgG MPh cja hCjf hgDdGA (B...s
(3BNQgG (B:s
...) (3nhobpd GrdnMoqb pef nqQqHocre (B( (3GdMb NHQ eHJOC eMPha (B. (3hGdeYfi (B: (3LGA GdMb hRGMJ GdYdd ade jHb EdG GNJjGQce dCfaSce eG TFJe ef GdCNP aj WQjb GdfLGI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\178s
(3cTa GdXfhf (B2\1475s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs